Deskripsi Hasil Belajar Siswa Melalui Penerapan Model Kreatif Produktif Pada Materi Pecahan Kelas VIIG MTS Negeri Masohi - Haris Kolengsusu (Jurnal Ilmiah Wahana Pendidikan, 2022)
The formulation of the problem in this study is how student learning outcomes are after the creative-productive learning model is applied to fractional material for class VII MTS Negeri Masohi. The purpose of this study was to describe student learning outcomes through the application of a creative-productive model in class VIIg MTs Negeri Masohi. The type of research used is descriptive quantitative research type. With the object of research which amounted to 25 students. The variable in this study is a single variable, namely student learning outcomes using productive creative models on fractional material. This research was conducted from August 22 to September 22, 2022. By using descriptive analysis and based on the results of the research, it can be concluded that applying a productive creative model can improve student learning outcomes. This can be seen from the learning outcomes of cognitive aspects, affective aspects, psychomotor aspects specifically in the final test given after the application of the creative productive model is categorized as very good because in this final test of the entire sample, namely 25 students have achieved KKM or the level of mastery has been completed.